The syntax of Old Norse : with a survey of the inflectional morphology and a complete bibliography - Faarlund, Jan Terje, 1943- (Oxford linguistics., 2004)
This is the first account of Old Norse syntax for almost a hundred years and the first ever in a non-Scandinavian language. The language of the Vikings and of the Old Icelandic sagas is the best documented medieval Germanic language: the author presents a full analysis of its syntax and overviews of its phonology and morphology. He includes a complete bibliography of Old Norse syntax. - ;This book offers the first account of Old Norse syntax for almost a hundred years and the first ever in a non-Scandinavian language. The language of the Vikings and of the Old Icelandic sagas is the best docum.